KONSTITUEN KIMIA MINYAK ATSIRI TIGA JENIS TUMBUHAN FAMILI RUTACEAE - Yuliasri Jamal; Sri Budi Sulianti (BERITA BIOLOGI, 2008)
Hydrodistilation process of Feroniella lucida, Clausena harmandiana and Swinglea glutinosa leaves, 0.15%, 0.25 % and 0.20% essential oils were obtained respectively. The GC-MS analysis results shows the essential oil of Feroniella lucida contains w-desil ethanoate (38.23%), 1-decanol (11.01%), 1-decanol acetate (10.82%), and the essential oil of Clausena harmandiana contains a-pinene (12.23%) and copaene (12.40%).On the other hand, the essential oil of Swinglea glutinosa contains isocariophylene (10.09%), 3,3,7,7-tetramethyl-5-(2-methyl-l-prophenyl)-tricyclo 4.1.0.02.4 heptane (21.80%) and nerolidol type 2 (21.34%).O